Membangun Resiliensi Spiritual Diaspora Indonesia Di Sapporo Melalui Edukasi Doa Bukan Last Option - Nesia Andriana; Dewi Anggrayni; Budi Handrianto; Wahidul Kholis Assaumi (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
This community service program aims to strengthen the spiritual understanding of the Indonesian diaspora community in Sapporo, Hokkaido, Japan, through hybrid-based Islamic study mentoring under the theme “Prayer Is Not a Last Option: The Essence, Virtues, and Power of Prayer.” The program was implemented through a partnership between the Graduate School of Universitas Ibn Khaldun Bogor and the Special Branch Leadership of Muhammadiyah Hokkaido / Pimpinan Ranting Istimewa Muhammadiyah (PRIM) Hokkaido. The implementation method began with a needs assessment through observation and communication with the partner institution to identify participants’ needs. The activities were then conducted using a hybrid method that combined lectures, discussions, halaqah, mentoring in muamalah studies, and Qur’anic tahsin training. The program was evaluated using a questionnaire to describe the participants’ level of understanding of the material presented. The results show that most participants understood the essence of prayer as a spiritual need, the relationship between prayer and effort, the importance of positive thinking toward Allah (husnuzan) in prayer, and the benefits of prayer in helping maintain inner peace and manage life pressures. The program also resulted in a commitment to sustainability through halaqah, muamalah studies, and tahsin training conducted in collaboration with the partner institution until the end of 2026. Thus, this community service program demonstrates that hybrid-based Islamic study mentoring can support the strengthening of spiritual understanding among the Indonesian diaspora community and serve as a sustainable mentoring model through collaboration between higher education institutions and community organizations.